EFFECT OF TIRZEPATIDE ON THE REDUCTION OF CARDIOVASCULAR OUTCOMES IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Souza e Silva, Pedro Henrique; Araújo, Francielly Ramos; dos Santos, Wesley Wagner; Freitas, Maria Fernanda Souza; da Costa, Anderson Alves; Queiroz, Gustavo Oliveira; Machado, Marjorie de Castro; Modesto, Géssica Gomes Pereira; Goes, Juan de Menezes; Feltrin, Daniel Gonçalves; Mamani, Ruben Enrique Flores; Barsella, Augusto Rafael; et al. (Seven Editora, 2026)
Type 2 Diabetes Mellitus (T2DM) represents a major global public health challenge due to its close association with cardiovascular morbidity and mortality. In this context, tirzepatide, a dual GIP and GLP-1 receptor agonist, has emerged as an innovative therapeutic approach in the cardiometabolic management of T2DM, demonstrating significant effects on glycemic control, weight reduction, and cardiovascular risk factors. This study aimed to critically analyze the available scientific evidence regarding the effects of tirzepatide on cardiovascular outcomes in individuals with T2DM. This integrative literature review was based on the methodological framework proposed by Whittemore and Knafl and conducted using PubMed/MEDLINE, Scopus, Web of Science, and ScienceDirect databases between March and April 2026. Studies published between 2016 and 2026 involving randomized clinical trials, meta-analyses, systematic reviews, observational studies, and narrative reviews related to the cardiovascular effects of tirzepatide were included. After applying the eligibility criteria, 13 studies composed the final sample. The findings demonstrated that tirzepatide promotes significant reductions in glycated hemoglobin (HbA1c), substantial weight loss, and consistent improvement in cardiometabolic parameters, including blood pressure, lipid profile, insulin resistance, and visceral adiposity. Furthermore, observational studies and meta-analyses suggested a favorable trend toward reduction of major adverse cardiovascular events and all-cause mortality, without evidence of increased cardiovascular risk. However, most currently available evidence derives from post-hoc analyses and studies with relatively short follow-up periods, limiting definitive conclusions regarding the magnitude of cardiovascular protection associated with tirzepatide. It is concluded that tirzepatide presents a promising cardiometabolic profile in the treatment of T2DM, although dedicated cardiovascular outcome trials are still required.